Penerapan Media E-Story Kesongo Berbasis Problem Based Learning dalam Pembelajaran Memahami Ide Pokok Siswa Kelas III SDN Pagerwojo - Mazida, Risma Nur; Purwati, Panca Dewi (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2026)
The low ability of elementary school students in identifying main ideas remains a challenge in Indonesian language learning. This condition is reflected in the number of students who have not yet achieved learning mastery. This study aimed to examine the implementation and effectiveness of Kesongo E-Story media based on Problem Based Learning (PBL) in improving third-grade students’ ability to understand main ideas. The research employed a mixed methods approach with quantitative and qualitative designs. The participants consisted of 21 third-grade students of SDN Pagerwojo 01 Kendal. Data were collected through pre-test, post-test, observation, and teacher response questionnaires. Quantitative data were analyzed using mean scores and N-Gain analysis, while qualitative data were analyzed descriptively. The findings indicated an improvement in students’ ability to understand main ideas after the implementation of PBL-based E-Story media. The students’ average score increased from 66.67 to 85.24, with an N-Gain score of 0.56 categorized as moderate. Learning mastery also improved from 66.67% to 100%. In addition, teachers gave positive responses to the media because it was considered engaging and encouraged students to participate more actively in the learning process. Based on these findings, Kesongo E-Story media based on Problem Based Learning can be used as an alternative learning medium to improve elementary school students’ ability to understand main ideas.